Exploration of EFL Teacher's Perception of Gender Awareness through Madurese Folktales with Critical Pedagogy Approach - Qadrina Lailyn Amrullah; Nur Ijabah (Universitas Islam Negeri Palopo, 2025)
Folktales often depict gender inequality, such as active and heroic male roles, while women are portrayed as passive. This representation has the potential to lead to unequal social treatment. By critiquing character portrayals, students can consider more equitable narratives. This study aims to reveal the perceptions of an EFL teacher in a vocational school in Pamekasan about gender awareness in Madurese folktales as a medium for critical pedagogy. Using the descriptive qualitative method, data were collected through interviews and analyzed using critical pedagogy theory. The results show that the teacher positively perceives folklore as a learning medium, especially in raising students' awareness of gender issues and improving critical thinking skills. Folktales are considered effective for improving students' learning motivation, language skills, and cultural understanding. In addition, folklore has the potential as a critical pedagogy tool that helps students analyze gender roles, challenge stereotypes, and build awareness of injustice, especially in the context of gender equality.